2020
DOI: 10.3389/fgene.2020.585999
|View full text |Cite
|
Sign up to set email alerts
|

Development of SNP-Based Genomic Tools for the Canadian Bison Industry: Parentage Verification and Subspecies Composition

Abstract: Genomic technologies have been increasingly applied in livestock production due to their utility in production management and animal genetic improvement. The current project aimed to develop genomic resources for the Canadian bison industry, specifically a parentage verification tool and a subspecies composition tool. Both products stand to help with building and maintaining purebred and crossbred bison populations, and in turn bison conservation and production. The development of this genomic toolkit proceede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Correct pedigree relationships are helpful for linkage map construction, core germplasm conservation, and breeding [ 10 ]. PE is a favorable parameter for evaluating kinship identification [ 37 ]. In this study, three types of PE (Q1, Q2, and Q3) for increasing combinations of the 45 markers had values of 100%, which showed that the parentage of the 117 tea cultivars could be accurately verified.…”
Section: Discussionmentioning
confidence: 99%
“…Correct pedigree relationships are helpful for linkage map construction, core germplasm conservation, and breeding [ 10 ]. PE is a favorable parameter for evaluating kinship identification [ 37 ]. In this study, three types of PE (Q1, Q2, and Q3) for increasing combinations of the 45 markers had values of 100%, which showed that the parentage of the 117 tea cultivars could be accurately verified.…”
Section: Discussionmentioning
confidence: 99%
“…Following similar strategies from this study, we can evaluate multiple bison herds to assess the presence of domestic cattle genomics and determine the genetic diversity and uniqueness of these herds, which can act as candidates to establish new conservation satellite herds. Indeed, a recent study made use of our sequencing, and a similar strategy to identify additional SNOs and to create a SNP-based parentage test and subpopulation composition in the Canadian bison industry (Yang et al, 2020). Following similar criteria and additional samples to better understand the genomic relationships between bison herds will aid with the relocation of bison herds when parks or herds have reached their carrying capacity.…”
Section: Discussionmentioning
confidence: 99%
“…The six historical bison samples were handled and stored separately from the modern samples and DNA was extracted in a UV killing isolation station with dedicated equipment and reagents as described by Curry and Derr 39 . Most of the genomic libraries were prepared and sequenced by Delta Genomics (Edmonton, Alberta, Canada) using the methods described by Yang et al 41 . Additional genomic libraries (Mackenzie Bison Sanctuary, Vermejo Park Ranch, and Yellowstone_1925) were prepared by Texas A&M AgriLife Genomics and Bioinformatics Service (College Station, TX) and sequenced using the Illumina NovaSeq 6000 platform.…”
Section: Methodsmentioning
confidence: 99%